A behavioral and serological survey on HIV prevalence among trucks drivers and sex workers in Benin - HESSOU, Septime; DOUGNON, Victorien; IMOROU, Ali; GLELE AHANHANZO, YOLAINE; AHOUSSINOU, Clément; ZANNOU, Marcel D; BABA MOUSSA, Lamine (My University, 2017)
Background: Between 2006 and 2012, the HIV rate in Benin remained stable at 1.2%, with some variation occurring between different segments of the population. It is known that truck drivers and clients of female sex workers (FSWs) are at higher risk for HIV infection. Objectives: This study seeks to better understand the changes in behavioral and serological indicators of HIV infection within these two social groups. Materials and Methods: We use descriptive and statistical methods to analyze cross-sectional data from gathered from all major population centers in Benin. Out of the 1400 commercial sex clients expected to enroll in the survey, 1008 participated, which represents an enrollment rate of 72%. In addition, 865 truck drivers participated in the study, which was carried out in 2015. Data were collected using an interview questionnaire and through blood samples. Results: Most truck drivers (80.2%) and clients of FSWs (88.0%) are Beninese and, for both groups, the average age was 29. The survey results also indicate that 12.1% of commercial sex clients and 8.8% of truckers had used drugs at least once in the past. In addition, 51.2% of clients of FSWs had recently been sexually active with multiple partners, and 43.4% had visited a FSW. In the case of truck drivers, 44.4% declared having recently had intercourse with multiple partners and 20.0% had paid for sex. In total, 79.5% of commercial sex users and 59.4% of truck drivers are well-informed about HIV/AIDS. Moreover, the survey data indicate that HIV rates in both groups dropped in comparison to 2012: HIV prevalence among clients of FSWs fell from 2.3% to1.3% and, in the case of truck drivers, from 3.2% to 1.2%. Conclusion: The results of our study highlight the need to reinforce programs and communication strategies that aim to raise awareness among clients of FSWs and truck drivers about HIV prevention measures.
Keywords: Behavioral and Serological Indicators; HIV/AIDS; Truck Drivers; Clients of Female Sex Workers